Apolipoprotein E genotype status affects habitual human blood mononuclear cell gene expression and its response to fish oil intervention. Issue 7 (20th April 2016) - Matualatupauw, Juri C.; Radonjic, Marijana; van de Rest, Ondine; de Groot, Lisette C. P. G. M.; Geleijnse, Johanna M.; Müller, Michael; Afman, Lydia A.
Abstract : We aim to gain insight into the effects of the apolipoprotein E4 ( APOE4) single nucleotide polymorphism on gene expression pathways, at baseline and on the response to fish‐oil supplementation. APOE4 carriers have higher expression of IFN signaling and cholesterol biosynthesis pathways at baseline. Fish‐oil supplementation causes a decrease in gene expression of the IFN signaling pathway in APOE4 carriers and an increase in noncarriers. Our findings provide new leads on the link between APOE4 genotype and cardiovascular disease (CVD) and on APOE4 genotype and CVD prevention using fish‐oil supplementation. Abstract : Scope: People who carry the apolipoprotein E4 ( APOE4 ) single nucleotide polymorphism have an increased risk of cardiovascular disease (CVD). Fish‐oil supplementation may help in the prevention of CVD, though interindividual differences in the response to n ‐3 PUFAs have been observed. We aimed to assess the impact of APOE genotype on peripheral blood mononuclear cell whole genome gene expression at baseline and following a fish‐oil intervention. Methods and results: Participants received 6 months of fish‐oil supplementation containing 1800 mg of eicosapentaenoic acid and docosahexaenoic acid per day. APOE genotype and peripheral blood mononuclear cell whole genome gene expression before and after supplementation were measured. We characterized the differences in gene expression profiles in carriers of APOE4 (N = 8 ) compared to noncarriers ( N = 15). At baseline, 1320 genes were differentially expressed and the fish‐oil supplementation differentially regulated 866 genes between APOE4 carriers and noncarriers. Gene set enrichment analysis showed that carriers had a higher gene expression of cholesterol biosynthesis and IFN signaling pathways. Fish‐oil supplementation reduced expression of IFN‐related genes in carriers only. Conclusion: The increased expression of IFN signaling and cholesterol biosynthesis pathways might explain part of the association between APOE4 and CVD. Fish‐oil supplementation may particularly benefit APOE4 carriers by decreasing expression of IFN‐related genes.